The Effect of Feedback in English Language Education - Semerci, Nuriye; Semerci, Nuriye (Iclel Conferences, 2016)
The significance of English Language within the world, as well as in Turkey, reveals the importance of language teaching and evaluation techniques within the learning-teaching process. Through the whole process, feedback is claimed to hold an important place as it forms the basis for understanding the missing aspect of learning-teaching process. The aim of this study is to examine the effect of feedback on the students' success in grammar and writing skills. For this purpose, 36 students were taken into the analysis -19 being the experimental group and 17 being the control group. The students were given a pre and post-test on their grammatical skills, and a post-test on their writing skills. In between the pre and post-tests the students went through a process in which they did some writing practices on some specific grammar topics they were tested on, and the experimental group took feedback during this process while the control group didn't. As a result, the variables collected through the pre and post tests were analyzed through non-parametric tests MWU and Wilcoxon. Finally, the results of the study revealed that feedback wasn't effective on the students' overall success in grammar as well as writing.
2nd International Conference on Lifelong Education and Leadership for All (ICLEL) -- JUL 21-23, 2016 -- Liepaja Univ, Liepaja, LATVIA
Keywords: Feedback; English Language; English Language Education